Sensitivity of neural stem cell survival, differentiation and neurite outgrowth within 3D hydrogels to environmental heavy metals. (3rd February 2016) - Tasneem, Sameera; Farrell, Kurt; Lee, Moo-Yeal; Kothapalli, Chandrasekhar R.
Highlights: Toxic effects of Cd, Hg and Pb on embryonic rat NSCs investigated. NSCs exposed to metals within 3D collagen gels, continuously for 14 days. Exposure duration and metal dose influenced NSC survival, differentiation and neurite outgrowth. Observed degree of toxicity is in the order: lead > mercury > cadmium. Mechanisms by which metal ions affect cell phenotype investigated. Abstract: We investigated the sensitivity of embryonic murine neural stem cells exposed to 10 pM–10 μM concentrations of three heavy metals (Cd, Hg, Pb), continuously for 14 days within 3D collagen hydrogels. Critical endpoints for neurogenesis such as survival, differentiation and neurite outgrowth were assessed. Results suggest significant compromise in cell viability within the first four days at concentrations ≥10 nM, while lower concentrations induced a more delayed effect. Mercury and lead suppressed neural differentiation at as low as 10 pM concentration within 7 days, while all three metals inhibited neural and glial differentiation by day 14. Neurite outgrowth remained unaffected at lower cadmium or mercury concentrations (≤100 pM), but was completely repressed beyond day 1 at higher concentrations. Higher metal concentrations (≥100 pM) suppressed NSC differentiation to motor or dopaminergic neurons. Cytokines and chemokines released by NSCs, and the sub-cellular mechanisms by which metals induce damage to NSCs have been quantified and correlated to phenotypic data. The observed degree of toxicity in NSC cultures is in the order: lead > mercury > cadmium. Results point to the use of biomimetic 3D culture models to screen the toxic effects of heavy metals during developmental stages, and investigate their underlying mechanistic pathways.